RANAH PENGGUNAAN BAHASA JAWA OLEH KALANGAN KELUARGA MUDA DI EKS KARASIDENAN SEMARANG - Retno Hendrastuti (Kantor Bahasa Provinsi Gorontalo, 2017)
The Javanese language is one of the Indonesian local languages with thelargest speakers. Meanwhile, there is anxiety that has been rise lately about the existence of Javanese language since the use of it in communication had been drastically decreased. This research uses mixed methods of qualitative and quantitative to obtain the areas and reasons why the Javanese language had been used among young marrie couples in ex-Semarang regency. The result of the study showed that the use of Javanese language found in six areas; familyhood, neighborhood, working area, friendship, trading area, and public space. The reasons of the using of Javanese language is simply because the majority of the society were native speakers; so it has been commonly using since early age; to develop warm and unformal relationship; to give language lesson and example to children and to other people; the expression of politeness and honors; to eliminate awkward and overact feeling when use Indonesian language, so that the communication would be easier to understand.